Striking differences in estimates of infant adiposity by new and old DXA software, PEAPOD and skin‐folds at 2 weeks and 1 year of life. Issue 4 (22nd July 2015) - Barbour, L. A.; Hernandez, T. L.; Reynolds, R. M.; Reece, M. S.; Chartier‐Logan, C.; Anderson, M. K.; Kelly, T.; Friedman, J. E; Van Pelt, R. E.
Summary: Background: Infant adiposity better predicts childhood obesity/metabolic risk than weight, but technical challenges fuel controversy over the accuracy of adiposity estimates. Objective: We prospectively measured adiposity (%fat) in term newborns (NB) at 2 weeks ( n  = 41) and 1 year ( n  = 30). Methods: %fat was measured by dual X‐ray absorptiometry (DXA), PEAPOD and skin‐folds (SF). DXAs were analyzed using Hologic Apex software 3.2(DXAv1) and a new version 5.5.2(DXAv2). Results: NB %fat by DXAv2 was 55% higher than DXAv1 (14.2% vs. 9.1%), 45% higher than SF (9.8%), and 36% higher than PEAPOD (10.4%). Among NB, Pearson correlations were 0.73–0.89, but agreement (intra‐class correlations) poor between DXAv2 and DXAv1 (0.527), SF (0.354) and PEAPOD (0.618). At 1 year, %fat by DXAv2 was 51% higher than DXAv1 (33.6% vs. 22.4%), and twice as high compared with SF (14.6%). Agreement was poor between DXAv2 and DXAv1 (0.204), and SF (0.038). The absolute increase in %fat from 2 weeks to 1 year was 19.7% (DXAv2), 13.6% (DXAv1) and only 4.8% by SF. Conclusion: Analysis of the same DXA scans using new software yielded considerably higher adiposity estimates at birth and 1 year compared with the previous version. Using different modalities to assess body composition longitudinally is problematic. Standardization is gravely needed to determine how early life exposures affect childhood obesity/metabolic risk.